The role of poetry translation in the reception of 17th-century English metaphysical poetry in Poland. Overview of issues - Banaszak, Michał (In Gremium. Studies in History, Culture and Politics, 2019)
The metaphysical poetry of the 17th century has become widespread in the English-speaking world mostly due to the influence of T.S. Eliot. However, the cross-section translations of this poetry into Polish began to be published in the second half of the XXth century. Among the authors of the most importatnt translations are Jerzy Pietrkiewicz, Jerzy S. Sito and Stanisław Barańczak. The purpose of this paper is to characterise the problems connected with the fact, that the reception of the metaphysical poets in Poland is determined by the translators’ choices. Not only readers, but literary scholars also rely their perception – to some extent – on translations. In this regard, translations by only one author – Barańczak – seem to have canonical status.. Another important issue is diversity of the metaphysical poets, constituting a challenge for the translator, who wants to maintain individual style of each member of this group. Moreover, metaphysical poetry creates an opportunity of discussion about the strategies of translating old poetry.